(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Online marketing methods used by companies to book hotels on business trips are subjects of reflection in the literature, in common sense and in some empirical studies. This article is also a theoretical and conceptual contribution to companies and managers on the subject, as it presents the results of an online study, of a quantitative nature, based on a sample of 206 Indian business executives who answered a questionnaire on social networks. Facebook, LinkedIn and Twitter, from May 20th to 28th, 2022. The objective of the research was to comparatively analyse the methods of booking hotels in business to business (B2B) with the aim of measuring the importance of the internet in these markets in India.